Islamic Sociopreneurship: Prophetic Principles and BAZNAS’s Approach in Empowering Mustahik - Mundzir, Muhammad; Muttaqin, Zaenal; Nadia, Matsna Afwi; Muttaqin, Azka (Fakultas Ekonomi dan Bisnis Islam UIN Walisongo, 2024)
The increasing unemployment and social inequality in Indonesia have prompted the investigation of creative strategies to improve welfare and social fairness. This study examines Islamic sociopreneurship—a business model derived on the ideas of the Prophet Muhammad—as a viable approach to tackle these difficulties by promoting self-sufficiency and generating social benefit. The research employs thematic and historical methodologies to analyze essential sociopreneurial principles drawn from the Prophet’s activities, encompassing capital management, resource usage, opportunity recognition, ethical decision-making, and innovation. These principles are used in effective zakat programs administered by BAZNAS, an Indonesian organization dedicated to poverty alleviation. The research indicates that BAZNAS’s initiatives substantially boost the livelihoods of mustahik (zakat recipients) by improving housing, augmenting income, and fostering the development of micro, small, and medium-sized enterprises (MSMEs). This research distinctly emphasizes the congruence of prophetic concepts with contemporary zakat practices, illustrating Islamic sociopreneurship as a viable framework for social empowerment and communal advancement.